Hexavalent Chromium and Cellular Bioenergetics: An Experimental Study - Shil , Kanu; Pal, Sudipta (Current Topics on Chemistry and Biochemistry Vol. 5, 2022)
The dose-dependent effect of sub-acute Cr(VI) exposure on carbohydrate bioenergetics was studied in mice. Blood glucose, liver glycogen and pyruvic acid, TCA cycle enzymes were examined. Additionally, NADH dehydrogenase activity, tissue protein content, free amino acid nitrogen and transaminase activities were also estimated. Chromium exposure caused marked depletion of blood glucose and liver glycogen in a dose-dependent manner. The activities of isocitrate dehydrogenase, succinate dehydrogenase and malate dehydrogenase were significantly altered in a dose specific manner. Exhaustion of pyruvate level was noted in hepatic tissue. Additionally, increased hepatic free amino nitrogen was associated with depletion of total protein, elevated transaminase activities and decreased NADH dehydrogenase activity. It is concluded that Cr(VI) exerts hypoglycaemic and glycogenolytic effects associated with alteration of TCA cycle and electron transport pathways in hepatocytes in a dose-specific manner resulting in alteration in carbohydrate bioenergetics.